Analysis of soil water biophysicochemical content from temporary waste disposal places - Endang Surahman; Mufti Ali; Vita Meylani (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
Population growth is in line with the increasing volume of waste generated, so that it has an impact on the increase in the location of landfills in temporary disposal sites (TPS) and landfills (TPA). Piles of runny rubbish often cause the degradation of groundwater quality. This study aims to determine the biological, physical, and chemical properties of groundwater originating from one of the TPS with different depths and distances. The research method used is an experiment which is further described qualitatively. This research was conducted at the Laboratory of Botany, Department of Biology, Universitas Siliwangi for four months. The material used in this study is ground water taken from one of the polling stations in the City of Tasikmalaya with different distances and depths. The instrument used was the observation guide analysed at PT Sucofindo. Based on the results of the study it can be concluded that all parameters observed are biological content, physical content and chemical content in groundwater as a whole polluted by alkali.